Strategi Penilaian dan Evaluasi Efektif Untuk Meningkatkan Kemampuan Siswa Serta Umpan Balik Dalam Pembelajaran Bahasa Indonesia - Ayu Atikah; Ivoni Amelia (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Assessment and evaluation in the context of Indonesian learning plays an important role in assessing and improving the quality of student learning. Effective assessments not only provide an overview of a student's abilities but also provide constructive feedback to improve learning outcomes. Specific and timely feedback, as well as technology integration, are critical to improving assessment efficiency. The differentiation approach is discussed to adapt the assessment strategy to the individual needs of the students. Overall, an assessment approach that is inclusive, competency-oriented, and relevant to the times is expected to help students prepare for global challenges.